LAJU PERTUMBUHAN PUYUH (Coturnix coturnix japonica) SETELAH PEMBERIAN TEPUNG KUNYIT (Curcuma longa) PADA PAKAN - Sylvia Frida Jamelah; Koen Praseno; Tyas Rini Saraswati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Research on The Growth Rate of The Japanese Quail (Coturnix coturnix japonica) After the Addition of Turmeric Powder (Curcuma longa) on Feed the animal test subjects were the Japanese quails (Coturnix coturnix japonica) which grouped into several treatment groups i.e. P0 (group of quails fed with standard feeding), P1 (group of quails fed with standard feeding which then added with turmeric powder 54 mg/head/day on age 14 to 44 days old), and P2 (group of quails fed with standard feedingwhich then added with turmeric powder 54 mg/head/day on age 14 to 120 days old), while parameters measurement was carried out for 4 months. The main observed parameter was weight increment which measured every once a week starting from 7 days old quails in each treatment group, while proponent parameters were feed and water intake. Measurement of weight was done using scaleon each quail in battery cages. The growth rate was obtained by calculating the difference between last week weight with first week weight per unit time, and was done on each quail in battery cages. Obtained data was analyzed using Analysis of variance (ANOVA) on the basis of a completely randomized design (CRD). If there was a difference among the treatments then proceed with further testing, using Duncan Test at a significance level of 95%. Based on the analysis of variance, it showed that there was a significant difference on feed intake while the growth rate didn’t indicate significant difference. Based on these results, it can be concluded that the turmeric powder as feed additive has no potential to increase the weight and the growth rate of the Japanese quail. Key words: Growth Rate, Quail (Coturnix coturnix japonica), turmeric powder (Curcuma domestica)